Soil carbon storage in rangeland ecosystems: The role of land management, climate change, and soil chemical transformations - Bidast, Solmaz; Golchin, Ahmad (Geoderma Regional, 2025)
Comprehension of the complex relationship between climate variations and soil characteristics is crucial for effectively managing soil organic carbon stocks (SOCs). This study involved a comprehensive analysis of soil properties, including sequential extraction of pedogenic oxides and carbon fractionation, across three distinct land management types: grazing land, undisturbed rangeland, and cultivated rangeland (cropland). Using the RothC model, projections were made to assess changes in SOC over a 63-year period under three different climate scenarios: baseline climate, warm-dry, and cool-wet scenarios. The findings revealed a strong linear correlation between observed and modeled SOC values for each management practice. Without climate change, the model predicted a 4.21 % decrease in SOC for cropland and a 2.37 % decrease for grazing land, while undisturbed rangeland showed a 3.04 % increase. Under the warm-dry scenario, all sites experienced a decline in SOC, whereas under the cool-wet scenario, SOC increased uniformly across all sites. In contradistinction to cropland and grazing land, undisturbed rangeland exhibited unique characteristics due to its long-term exposure to weathering. These included a significant increase in the chemical index of alteration, higher levels of occluding carbon within the microaggregates fraction, and varied amounts of dithionite and oxalate-extractable aluminum and iron. These factors enhanced the physical protection of SOC from microbial decomposition. This was supported by positive correlations between SOC and these factors, as well as the humified organic matter pool. In summary, understanding the relationship between management practices, climatic conditions, and the mechanisms that govern SOC conservation is pivotal for judicious decision-making. [Display omitted]